Cultura contable como aporte al proceso de toma de decisiones de los emprendedores; caso de la organización de la red de productores manuales de El Oro Ecuador Orpromaoro-Ec. - Yaguana Calva, Mishel Geomayra; Bombon Cardenas, Ana Belen (Machala : Universidad Técnica de Machala, 2025)
This study analyzes the influence of accounting culture on the economic decision-making processes of entrepreneurs belonging to the organization ORPROMAORO-EC, located in the province of El Oro, Ecuador. Through a quantitative approach, structured surveys were conducted with the 16 members of the organization, evaluating eight key subdimensions: accounting principles, accounting process, IFRS standards, tax regulations, planning, management, execution, and control. The results show that although entrepreneurs partially recognize the importance of accounting culture, there are significant deficiencies in its practical application—particularly in the use of international standards and basic accounting tools. These limitations affect the quality of available financial information and, consequently, the effectiveness of their business decisions. The research proposes a strategic action plan aimed at strengthening the accounting, tax, and administrative competencies of entrepreneurs through training programs, participatory methodologies, and evaluation tools. It concludes that a solid accounting culture is essential to enhance the sustainability, transparency, and competitiveness of entrepreneurial initiatives within the framework of the popular and solidarity economy.
Este estudio analiza la influencia de la cultura contable en la toma de decisiones económicas de los emprendedores pertenecientes a la organización ORPROMAORO-EC, en la provincia de El Oro, Ecuador. A través de un enfoque cuantitativo, se aplicaron encuestas estructuradas a los 16 socios de la organización, evaluando ocho subdimensiones clave: principios contables, proceso contable, normas NIIF, normativa tributaria, planificación, dirección, ejecución y control. Los resultados evidencian que aunque los emprendedores reconocen parcialmente la importancia de la cultura contable, existen deficiencias en su aplicación práctica especialmente en el uso de normas internacionales y herramientas contables básicas. Esta limitación afecta la calidad de la información financiera disponible y, por ende, la efectividad de sus decisiones empresariales. La investigación propone un plan de acción estratégico orientado a fortalecer las competencias contables, tributarias y administrativas de los emprendedores, mediante capacitaciones, metodologías participativas y herramientas de evaluación. Se concluye que una cultura contable sólida es esencial para mejorar la sostenibilidad, transparencia y competitividad de los emprendimientos en el contexto de la Economía Popular y Solidaria.
Keywords: CULTURA CONTABLE; TOMA DE DECISIONES; EMPRENDEDORES